Analisis Yuridis Tindak Pidana Pembunuhan Berencana yang Dilakukan Secara Bersama-Sama di Tinjau dari Ketentuan Pasal 340 KUHP ketentuan Pasal 340 KUHP - Sanmas, Rusdi (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2023)
Indonesia adheres to the supremacy of law as the front guard towards a welfarstate (welfare state) as stated in the 4th paragraph of the Preamble to the 1945 Constitution of the Republic of Indonesia which mandates the protection of the entire Indonesian nation, which also protects in terms of law enforcement. In order to realize these ideals, in a state it is necessary to regulate norms or rules that are public in nature and apply nationally as a control mechanism for its citizens. One of the public regulations is the regulation that contains criminal law. Based on the background, problem identification, the problem can be formulated with the following research questions; Will the perpetrator be deterred in cases of premeditated murder? What are the judge's legal considerations in deciding a criminal case of premeditated murder?